City life satisfaction: a measurement for smart and sustainable cities from the citizens' perspective. (11th February 2020) - Silva, Marcelo Benetti Correa Da; Bebber, Suélen; Fachinelli, Ana Cristina; Moschen, Suane De Atayde; Perini, Rafael De Lucena
The study aims to contribute to the current panorama of instruments that qualify cities by presenting an approach of sustainable goals and indicators. Insight from inhabitants about their cities reveal dimensions and attributes not captured by official indicators. The focus of this study is to define appropriate indicators for sustainability and smartness of cities according to their citizens, considering the idiosyncrasies of local contexts and less notable dimensions pointed out in earlier studies. The scale is based on consolidated metrics, such as the UN Sustainable Development Goals, and the ISO 37120/2017, in association with the European Barometer and American Barometer. The CITYLIFESAT (City Life Satisfaction) scale was tested and validated in Southern Brazil through exploratory and confirmatory factor analysis, and discriminant analysis. The results show that citizens' satisfaction is primarily linked to health and safety, well-being, recreation, public transport, walkability, social inclusion and participation, primary services, city attachment, and environment.